Survival and Prognostic Factors in Patients With Solid Pseudopapillary Neoplasms of the Pancreas. Issue 8 (September 2018) - Huffman, Brandon M.; Westin, Gustavo; Alsidawi, Samer; Alberts, Steven R.; Nagorney, David M.; Halfdanarson, Thorvardur R.; Mahipal, Amit
Abstract : Objectives: Prognostic factors for solid pseudopapillary neoplasms (SPN) of the pancreas have been incompletely defined in the literature. We aimed to use the National Cancer Database to describe survival and characterize prognostic factors in patients with pancreatic pseudopapillary neoplasms. Methods: We identified 304 patients with pancreatic SPN diagnosed between 2004 and 2012 using the National Cancer Database. All patients were included in the survival analysis. Kaplan-Meier method, χ 2, and log-rank tests were used for statistical analysis. Cox proportional hazard regression model was used for multivariate analysis. Results: The median age at diagnosis was 36.5 years. Eighty-five percent of patients were female, 69% were white, and 25% were black. Metastases were observed in 5% of patients. Median tumor size was 5.1 cm. Ninety-two percent of patients underwent primary tumor resection. At 60 months, 98% of patients who underwent resection were alive, and 40% who did not undergo resection were alive. On multivariate analysis, female sex, resection of primary tumor, and absence of metastasis were correlated with improved survival. Conclusions: Patients with SPN who undergo resection have an excellent survival at 5 years. Surgery should be considered in all patients with this diagnosis.